2016
DOI: 10.5400/jts.2015.v20i1.1-9
|View full text |Cite
|
Sign up to set email alerts
|

The Nutrient Uptake Efficiency, Crop Productivity and Quality of Rice Bean in Dry Land

Abstract: Rice bean is a group of beans that are rich in carbohydrates, proteins and fats. This plant is resistant to pests and diseases, as well as the broad adaptability.  This study aims to obtain an efficient fertilization pattern on rice bean cultivation in dry land. The treatments consisted of 9 fertilization patterns which were RP0: no fertilizer (control); RP1: 100%  recommendation fertilizer (50 kg Urea and 100 kg SP-36 ha-1); RP2: 5 Mg ha-1 manure plus 50% recommendation fertilizer; RP3: RP2 plus MVA; RP4: 5 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Although average values of the parameters were found to be different among treatments, statistically, these values were not significantly different, i.e., these values are at par with each other, which might be due to previous field conditions, extraneous soil factors, soil fertility gradient, soil moisture content, soil heterogeneity, soil texture, environmental factor, etc Swathi et al (2021). reported that the application of 20 kg K/ ha plus 15 kg Fe/ha produces an optimum level of plant parameters encompassing plant height, nodules per plant, plant dry weight, branches per plant, pods per plant, and seeds per pod.During an investigation on rice beans,Susilowati et al (2016) reported that the combination of 5 Mg organic fertilizer, 50% of recommended fertilizer, plus MVA induces the productivity and quality of the rice bean crop. Furthermore,Ponmurugan et al (2016) also documented that using plant growth-promoting microbes, particularly actinomycetes, increases the growth performance and production ability in Vigna by boosting nitrogen availability and metabolism.…”
mentioning
confidence: 99%
“…Although average values of the parameters were found to be different among treatments, statistically, these values were not significantly different, i.e., these values are at par with each other, which might be due to previous field conditions, extraneous soil factors, soil fertility gradient, soil moisture content, soil heterogeneity, soil texture, environmental factor, etc Swathi et al (2021). reported that the application of 20 kg K/ ha plus 15 kg Fe/ha produces an optimum level of plant parameters encompassing plant height, nodules per plant, plant dry weight, branches per plant, pods per plant, and seeds per pod.During an investigation on rice beans,Susilowati et al (2016) reported that the combination of 5 Mg organic fertilizer, 50% of recommended fertilizer, plus MVA induces the productivity and quality of the rice bean crop. Furthermore,Ponmurugan et al (2016) also documented that using plant growth-promoting microbes, particularly actinomycetes, increases the growth performance and production ability in Vigna by boosting nitrogen availability and metabolism.…”
mentioning
confidence: 99%